Clearance of therapeutic antibody glycoforms after subcutaneous and intravenous injection in a porcine model. Issue 1 (31st December 2022) - Falck, David; Lechmann, Martin; Momčilović, Ana; Thomann, Marco; Koeleman, Carolien A. M.; Jany, Cordula; Malik, Sebastian; Wuhrer, Manfred; Reusch, Dietmar
ABSTRACT: A relatively low clearance is one of the prominent favorable features of immunoglobulin G1-based therapeutic monoclonal antibodies (mAbs). Various studies have observed differential clearance of mAb glycoforms, including oligomannose glycoforms, which are considered a critical quality attribute because they show higher clearance than complex type glycoforms. Glycoform clearance, however, has not previously been studied after subcutaneous injection or in a porcine model system. Here, we performed glycoform-resolved pharmacokinetic (PK) analysis of two mAbs in Göttingen minipigs. We found glycoform effects on clearance to be largely the same for subcutaneous and intravenous injection and in line with observations in other species. Oligomannose glycoforms were cleared up to 25% faster and monoantennary glycoforms up to 8% faster than agalactosylated complex glycoforms. Sialylated glycoforms were cleared at approximately the same rate as fully galactosylated glycoforms. Importantly, we report here an impact of galactosylation on the PK of a mAb for the first time. Whether increased galactosylation led to slower or faster clearance seemed to depend on the overall glycosylation profile. When clearance of galactosylated glycoforms was slower, the mAb showed higher galactosylation in serum at maximum concentration after subcutaneous injection compared to both intravenous injection and the injected material. Whether this higher galactosylation after subcutaneous injection has consequences for therapeutic efficacy remains to be investigated. In conclusion, preferential clearance of antibody glycoforms can be simulated in the minipig model with intravenous as well as subcutaneous injections. Furthermore, we observed a glycoform bias in the absorption from skin into circulation after subcutaneous injection based on galactosylation. Abbreviations : AUC - area under the curve; CL/F - apparent clearance as a function of bioavailability following SC administration; Cmax - maximum serum concentration; CQA critical quality attribute; FcγR - Fc gamma receptor; IgG - immunoglobulin G; IV - intravenous; LC-MS - liquid chromatography - mass spectrometry; mAb - therapeutic monoclonal antibody; PK - pharmacokinetics; SC - subcutaneous; TMDD - target-mediated drug disposition